Humanized Anti-hepatocyte Growth Factor Monoclonal Antibody (YYB-101) Inhibits Ovarian Cancer Progression - Kim, Hyun Jung; Lee, Sukmook; Oh, Yong-Seok; Chang, Ha Kyun; Kim, Young Sang; Hong, Sung Hee; Kim, Jung Yong; Park, Young-Whan; Lee, Song-Jae; Song, Seong-Won; Kim, Jung Ju; Heo, Kyun (Frontiers in Oncology, 2019)
Current chemotherapy regimens have certain limitations in improving the survival rates of patients with advanced ovarian cancer. Hepatocyte growth factor (HGF) is important in ovarian cancer cell migration and invasion. This study assessed the effects of YYB-101, a humanized monoclonal anti-HGF antibody, on the growth and metastasis of ovarian cancer cells. YYB-101 suppressed the phosphorylation of the HGF receptor c-MET and inhibited the migration and invasion of SKOV3 and A2780 ovarian cancer cells. Moreover, the combination of YYB-101 and paclitaxel synergistically inhibited tumor growth in an in vivo ovarian cancer mouse xenograft model and significantly increased the overall survival (OS) rate compared with either paclitaxel or YYB-101 alone. Taken together, these findings suggest that YYB-101 has therapeutic potential in ovarian cancer when combined with conventional chemotherapy agents.